Transnational Crimes and Human Trafficking: A Study of Humanitarian Crisis on Pak-Afghan Border - Mahwish Bakht; Sohail Ahmed; Muhammad Shehryar Khan (ASIAN Journal of International Peace & Security (AJIPS), 2022)
In the era of globalization, war has become a part of history, while, cooperation is the new normal and the state’s grand strategy. In developing countries, the continuum execution of military operations, low standards of socio-economic conditions for natives/ migrants, natural calamities, and complex forces against border security provide a conducive environment for the heinous expansion of human traffickers. Globally, Afghanistan and Pakistan have consistently maintained their higher ranking in global slavery index due to vulnerable security situation. Since 9/11 attacks have promoted socio-economic problems and challenged the peace-building efforts in Afghanistan. The study aims to explore the deep linkages of the rising threat of human trafficking and its consequences for both countries. This study elucidates that the fluctuations in building trust and conflicting national interests impeded the development of peaceful consensus on the regularization of the Pak-Afghan border, and; it has caused serious threats to the human security of both nationals. It also provides a cushion in the proliferation of human smugglers. This qualitative study involved a phenomenological approach for primary data collection while analysis is done via narrative and content analysis method.